2011
DOI: 10.1002/jwmg.224
|View full text |Cite
|
Sign up to set email alerts
|

Site occupancy and cavity use by the northern flying squirrel in the boreal forest

Abstract: Tree cavities are used as shelter and breeding nests by numerous avian and mammalian species. In cold environments, tree cavities are often proposed as the best winter nest choice because of the superior protection they offer from precipitation, wind, cold temperatures, and predators. As such, they represent a critical resource, which has the potential to limit population size of non‐excavating species. We assessed factors affecting site occupancy in the boreal forest by northern flying squirrels, a secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
4
15
0
Order By: Relevance
“…However, as expected based on a recent study (Trudeau et al 2011), we observed a positive effect of temperature on detection probability. The latter result is consistent with the observations of McComb and Noble (1981) on temperature being on average 6.5 • C colder inside nest boxes than inside cavities in a bottomland hardwood stand in Louisiana.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, as expected based on a recent study (Trudeau et al 2011), we observed a positive effect of temperature on detection probability. The latter result is consistent with the observations of McComb and Noble (1981) on temperature being on average 6.5 • C colder inside nest boxes than inside cavities in a bottomland hardwood stand in Louisiana.…”
Section: Discussionsupporting
confidence: 91%
“…All data were acquired from the closest meteorological station, which was located in the city of Val-d'Or (48 • 03 N, 77 • 47 W), and downloaded from the Environment Canada website (Environment Canada, 2009). Because cavity use decreases at low temperatures (Trudeau et al 2011), we expected a similar effect on nest box use, yielding a positive effect of temperature on probability of detection at our study sites. Because leaf nests are apparently constructed only in conifers in our study area (Trudeau et al 2011), we also expected that probability of detection of flying squirrels using nest boxes would be higher in sites where the availability of conifers is low.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Deciduous tree snags, and particularly those of poplars, are preferred by the pileated woodpecker, a keystone species that creates large cavities, which can further be used by other tree nesting species such as flying squirrels [86,87].…”
Section: Young Forests Community Types Descriptionmentioning
confidence: 99%
“…) and occupancy models (Trudeau et al. ) accounting for imperfect detectability suggest that highest northern flying squirrel population densities are not always linked to older stands, especially in mixed‐wood forests.…”
Section: Introductionmentioning
confidence: 99%